2018
DOI: 10.1021/acs.est.8b04582
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Oxidation of Chlorinated Organics over Lanthanide Perovskites: Effects of Phosphoric Acid Etching and Water Vapor on Chlorine Desorption Behavior

Abstract: In this article, the underlying eff ect of phosphoric acid etching and additional water vapor on chlorine desorption behavior over a model catalyst La3Mn2O7 was explored. Acid treatment led to the formation of LaPO4 and enhanced the mobility of lattice oxygen of La3Mn2O7 evidenced by a range of characterization (i.e., X-ray diff raction, temperature-programmed analyses, NH3−IR, etc.). The former introduced thermally stable Bronsted acidic sites that enhanced dichloromethane (DCM) hydrolysis while the latter fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
85
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(87 citation statements)
references
References 59 publications
2
85
0
Order By: Relevance
“…[49] Wu et al has demonstrated manganite layered perovskite i.e La 3 Mn 2 O 7 + δ as a model catalyst in the oxidation of chlorinated organic due to its high thermal stability and enriched oxygen species. [65,66] Tanaka et al has described the role of Pt-free Sr 3 Fe 2 O 7-δ (Ruddlesden-Popper oxide) as catalyst in NO x oxidation and storage reactions. [66]…”
Section: Layered Perovskite Oxides As Catalystmentioning
confidence: 99%
“…[49] Wu et al has demonstrated manganite layered perovskite i.e La 3 Mn 2 O 7 + δ as a model catalyst in the oxidation of chlorinated organic due to its high thermal stability and enriched oxygen species. [65,66] Tanaka et al has described the role of Pt-free Sr 3 Fe 2 O 7-δ (Ruddlesden-Popper oxide) as catalyst in NO x oxidation and storage reactions. [66]…”
Section: Layered Perovskite Oxides As Catalystmentioning
confidence: 99%
“…explored the influence of phosphoric acid etching and water steam on dichloromethane elimination over La 3 Mn 2 O 7 and found that the former enhanced dichloromethane hydrolysis and the latter promoted desorption of accumulative chlorine with elevated temperatures. 27 However, the study on CVOCs combustion over MnO 2 with different crystal planes is rare reported. What's more, how to improve the anti-poisoning ability of catalyst as well as avoid deactivation and producing more harmful by-products is still a challenge in industrial application.…”
Section: Introductionmentioning
confidence: 99%
“…In these transition metal oxides, ceria-based oxides, like CeO2-TiO2 [6] , CeO2-FeOx [5] , CeO2-CrOx [33,36] , CeO2-VOx [28,37] , CeO2-WOx [3] , and CeO2-MnOx [14,26,38] , have attracted more attention due to the high oxygen storage capacity, Ce 4+ /Ce 3+ redox properties of cerium oxide, and the strong interplay between MOx and CeO2. Recently, composite oxides as perovskitetype and spinel-type were also identified as feasible catalysts to complete catalytic oxidation of CVOCs ascribed to good thermal stability, good tolerance to chlorine poisoning, high oxygen mobility and relatively higher activities [39] . The perovskitetype oxides, such as LaCoO3 [4] and LaMnO3 [40] , are the commonest compounds for CVOCs oxidation.…”
Section: Introductionmentioning
confidence: 99%